TRIB3 supports breast cancer stemness by suppressing FOXO1 degradation and enhancing SOX2 transcription - Jin-mei Yu (Nature Portfolio, 2019)
Cancer stem cells contribute to breast cancer metastasis and recurrence. Here the authors show that TRIB3 enhances breast cancer stemness through interaction with AKT to promote FOXO1 stability, which then increases SOX2 activity.